Violence, neurocognitive function and clinical correlates in patients with schizophrenia - Yi, Yun; Huang, Yuanyuan; Chen, Qiang; Yang, Hanlun; Li, Hehua; Feng, Yangdong; Feng, Shixuan; Zhou, Sumiao; Li, Zezhi; Wu, Fengchun (Frontiers in Psychiatry, 2023)
Background: Schizophrenia patients with violent behavior are a severe public health concern, but the correlates of this violent behavior are unknown. Additionally, the relationship between neurocognitive function and violent behavior in Chinese patients with schizophrenia has not yet been investigated. Methods: A total of 337 schizophrenia inpatients were recruited. The Positive and Negative Syndrome Scale (PANSS) was used to assess psychopathological symptoms. Neurocognitive functioning was evaluated using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Results: The percentage of violent behavior was 10.4% in patients with schizophrenia. Patients with violent behavior had higher PANSS-positive, excited, and total subscale scores than patients who did not show violent behavior. Patients with violent behavior also had lower RBANS-language, semantic fluency, and total subscale scores. Gender (OR=0.066~0.819, p=0.023), illness duration (OR=0.876~0.971, p=0.002), smoking (OR=1.127~2.950, p=0.014), the PANSS positive subscale (OR=1.050~1.197, p=0.001) and the RBANS language subscale (OR=0.927~0.987, p=0.005) significantly contributed to the development of violent behavior in schizophrenia patients. Conclusions: Our findings revealed that cognitive and clinical assessments should be considered in comprehensive assessments of future risks of violence in schizophrenia patients.